Clinical Reasoning: A 25-Year-Old Woman With Eye Swelling and Headache. (2nd May 2023) - Hehir, Aoife; Gilmore, Ruth; Power, Sarah; Monaghan, Thomas; McGrath, Emer R.
Abstract : Cerebral venous sinus thrombosis (CVST) is uncommon. Risk factors include inherited and acquired factors. Rapid diagnosis and treatment is essential and can help prevent complications, which can include seizures and visual disturbance. A 25-year-old woman with a background history of CVST and intermittent warfarin use presented to the hospital in 2021 with a 3-month history of progressive eye swelling and headache. Her headache was located in the right frontal region and worsened with movement. Her workup was consistent with recurrent CVST and dural arteriovenous fistula. IR-guided embolization of the fistulas and stenting of her sinuses was performed. She was treated with dual antiplatelet therapy and therapeutic tinzaparin. Her symptoms improved markedly over several days, with improvement in headache and visual acuity. This case illustrates the potential for severe complications including visual disturbance in untreated CVST, as well as the importance of a thorough history and examination in aiding the recognition of the condition.